Cu(Ii) Extraction Using Quaternary Ammonium and Quaternary Phosphonium Based Ionic Liquid - Navarro-Donoso, P (2014)
This work analyses the extraction of Cu(II) using quaternary ammonium and quaternary phosphonium based ionic liquids. Firstly, the chemical suitability of the two ionic liquids was evaluated. They were then tested for extracting copper from solutions (simulated) of liquid mining waste. The effects of the extractant concentration, the sulphate concentration and the stripping solution were studied and the resulting information allowed us to propose a reaction mechanism. Finally, tests were performed using supported liquid membranes (SLM). The results with the synthesised ionic liquids show that [A336/Cy272] is suitable in sulphate, chloride and mixed media, while [C104] is suitable in chloride media. Liquid/liquid extraction tests indicate that it is possible to remove Cu(II) from highly contaminated aqueous solutions (1000 mg/L Cu(II)) using quaternary ammonium type ionic liquids in sulphate, chloride or mixed media, with extraction efficiencies of up to 95%. The best stripping results were obtained in basic and acid media. In contrast, a fouling problem of the membrane was found in supported liquid membrane tests, which occurs after approximately 4 h of testing. © 2013 Elsevier B.V.